Go-to-market strategy - Terziovski, Milé (Henry Stewart Talks, 2026)
Feasibility analysis for go-to-market strategy, Components of a go-to-market strategy, Steps involved in mapping the technology environment, Distribution channels, Promotional strategies, Creating a marketing plan, Importance of building relationships with early adopters and influencers